Determining Factors Influencing Increased Customer Retention at Pingpong Bites MSMEs in Malang - Furqanul Amirur Rifan; Abdur Rohman (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2026)
Customer retention is a crucial factor in ensuring business sustainability, especially for MSMEs in the culinary sector that face intense competition. This study evaluates various factors that contribute to enhancing customer retention at Pingpong Bites, an MSME based in Malang. The approach employed includes a systematic literature review (SLR) and semi-structured interviews with business owners and customers. The findings reveal that service quality, product quality, pricing and promotional strategies, as well as customer satisfaction, play vital roles in building loyalty. Additionally, product innovation and the ability to adapt to market trends are also essential aspects of maintaining customer engagement. These findings offer guidance for MSMEs in designing more effective strategies to increase customer loyalty and support sustainable business growth.